2009
DOI: 10.1063/1.3251073
|View full text |Cite
|
Sign up to set email alerts
|

Emission of Tamm plasmon/exciton polaritons

Abstract: We report on the observation of the strong coupling regime occurring between a Tamm plasmon (TP) mode and an exciton from inorganic quantum wells (QWs). The sample is formed by a silver thin film deposited onto an AlAs/GaAlAs Bragg reflector containing InGaAs QWs located in the high refractive index layers. Angular resolved reflectometry experiments evidence a clear anticrossing in the dispersion relations, a signature of the strong coupling regime. The Rabi splitting energy is 11.5 meV. The experimental data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
58
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(63 citation statements)
references
References 14 publications
4
58
0
1
Order By: Relevance
“…Note that recently strong coupling of Tamm plasmon and quantum well ͑QW͒ excitons has been demonstrated experimentally. 11 As with conventional surface plasmons, 12 TSPs can be strongly coupled to the optical cavity modes as we show here. The resonant coupling of the TSPs to cavity exciton polaritons results in the appearance of hybrid plasmonexciton-polariton modes forming a characteristic triplet.…”
mentioning
confidence: 67%
“…Note that recently strong coupling of Tamm plasmon and quantum well ͑QW͒ excitons has been demonstrated experimentally. 11 As with conventional surface plasmons, 12 TSPs can be strongly coupled to the optical cavity modes as we show here. The resonant coupling of the TSPs to cavity exciton polaritons results in the appearance of hybrid plasmonexciton-polariton modes forming a characteristic triplet.…”
mentioning
confidence: 67%
“…Moreover, the confinement in the dielectric multilayer structure is due to the photonic band gap of the Bragg mirror, instead of total internal reflection. Potential applications on TPPs [10][11][12][13][14][15][16][17] have been found in the realization of optical components, such as absorbers 10 , filters 11 , and bistable switches 12 . It has also been found that one can achieve strong coupling between TPPs and the excitons from a quantum well 13,14 or a quantum dot 15 , and possibly utilize these states in the construction of a polariton laser without a microcavity 16 .…”
Section: Introductionmentioning
confidence: 99%
“…mixed excitations bound to the surface of the Bragg mirror,-which exploit the confinement of the optical mode due to total internal reflection as weel as a photonic bandgap-could be exploited for prospective polariton devices with high efficiency and controlled long range propagation, or for applications requiring high surface sensitivity such as optical sensors, [13,14] with clear advantages over alternative structures where metal deposition is required. [15,16] In this letter we report on the experimental demonstra- tion of strong light-matter coupling between J-aggregate excitons with Bloch surface waves (BSW) at the interface between a SiO 2 /TiO 2 Bragg mirror and an index matching homogeneous medium. Evidence of polariton formation is reported by independently measuring reflectivity and emission spectra, which both show the typical anticrossing behavior as a function of the angle of inciarXiv:1401.4555v1 [cond-mat.mes-hall]…”
mentioning
confidence: 99%